Measured adiposity in relation to head and neck cancer risk in the European Prospective Investigation into Cancer and Nutrition. - Ward, H; Wark, P; Muller, D; Steffen, A; Johansson, M; Norat, T; Gunter, M; Overvad, K; Dahm, C; Halkjær, J; Tjønneland, A; Boutron-Ruault, M; et al. (American Association for Cancer Research, 2017)
Background Emerging evidence from cohort studies indicates that adiposity is associated with greater incidence of head and neck cancer (HNC). However, most studies have used self-reported anthropometry which is prone to error. Methods Among 363 094 participants in the European Prospective Investigation into Cancer and Nutrition study (EPIC) with measured anthropometry, there were 837 incident cases of HNC. HNC risk was examined in relation to body mass index (BMI) [lean: < 22.5 kg/m2, normal weight (reference): 22.5-24.9 kg/m2, overweight 25-29.9 kg/m2, obese: > 30 kg/m2], waist circumference (WC), hip circumference (HC) and waist to hip ratio (WHR) using Cox proportional hazards models. Results Among men, a BMI < 22.5 kg/m2 was associated with higher HNC risk [hazard ratio (HR) 1.62, 95% confidence interval (CI) 1.23 – 2.12)]; BMI was not associated with HNC among women. WC and WHR were associated with greater risk of HNC among women, (WC per 5 cm: HR 1.08, 95% CI 1.02 – 1.15; WHR per 0.1 unit: HR 1.64, 95% CI 1.38 – 1.93). After stratification by smoking status, the association for WHR was present only among smokers (p interaction 0.004). Among men, WC and WHR were associated with HNC only upon additional adjustment for BMI (WC per 5 cm: HR 1.16, 95% CI 1.07 – 1.26; WHR per 0.1 unit: HR 1.42, 95% CI 1.21 – 1.65). Conclusion Central adiposity, particularly among women, may have a stronger association with HNC risk than previously estimated.